The influence of cod-liver oil diet on various lipid metabolism parameters, the thromboxane formation capacity, platelet function and the serum MDA level in patients suffering from myocardial infarction - Kahl, P E; Schimke, E; Hildebrandt, R; Beitz, J; Schimke, I; Beitz, H; Mrochen, H; Mest, H J (Cor et vasa, 1987)
The influence of an eicosapentaenoic-acid-rich diet, containing 8.1 g cod-liver oil, given daily for two weeks on various parameters of lipid metabolism, the thromboxane formation capacity, platelet function and the serum MDA level was studied in 16 patients with myocardial infarction. The 18:2, 20:3 and 20:4 fatty acid portions of serum phospholipids were significantly decreased, whereas the 20:5 and 22:6 portions were significantly elevated. Serum total cholesterol, LDL cholesterol and the thromboxane formation capacity were significantly increased. Serum triglycerides, HDL cholesterol, the prostacyclin blocking activity of LDL, and several parameters of platelet function were unchanged, the platelet count was significantly depressed. As compared to those of healthy persons, the serum MDA levels in myocardial infarction patients were significantly increased both before and after cod-liver oil ingestion. A possible correlation between the elevated serum levels of MDA and total cholesterol, LDL cholesterol as well as thromboxane formation capacity and the cod-liver oil treatment in patients with myocardial infarction is discussed.
Keywords: Thromboxanes; cholesterol; lipoproteiny; triglyceridy; thromboxany; Cod Liver Oil; lipidy; Fish Oils; Platelet Aggregation; Triglycerides; lidé; Lipids; agregace trombocytů; Cholesterol; Male; rybí tuk; Malondialdehyde; Myocardial Infarction; malonáty; malondialdehyd; lidé středního věku; Lipoproteins; mužské pohlaví; Malonates; rybí oleje; Middle Aged; infarkt myokardu; Humans